IDNLearn.com makes it easy to find answers and share knowledge with others. Ask your questions and receive reliable, detailed answers from our dedicated community of experts.
Sagot :
Certainly! Let's solve the equation [tex]\(\sqrt{x + 9} - x = 9\)[/tex] step-by-step and verify the solutions.
1. Start with the given equation:
[tex]\[ \sqrt{x + 9} - x = 9 \][/tex]
2. Isolate the square root on one side of the equation:
[tex]\[ \sqrt{x + 9} = x + 9 \][/tex]
3. Square both sides of the equation to eliminate the square root:
[tex]\[ (\sqrt{x + 9})^2 = (x + 9)^2 \][/tex]
4. Simplify both sides:
[tex]\[ x + 9 = (x + 9)^2 \][/tex]
5. Expand the right side of the equation:
[tex]\[ x + 9 = x^2 + 18x + 81 \][/tex]
6. Bring all terms to one side to set the equation to zero:
[tex]\[ 0 = x^2 + 18x + 81 - x - 9 \][/tex]
7. Simplify the equation:
[tex]\[ 0 = x^2 + 17x + 72 \][/tex]
8. Solve the quadratic equation [tex]\(x^2 + 17x + 72 = 0\)[/tex].
The quadratic formula is given by [tex]\(x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\)[/tex]. Here, [tex]\(a = 1\)[/tex], [tex]\(b = 17\)[/tex], and [tex]\(c = 72\)[/tex].
[tex]\[ x = \frac{-17 \pm \sqrt{17^2 - 4 \cdot 1 \cdot 72}}{2 \cdot 1} \][/tex]
[tex]\[ x = \frac{-17 \pm \sqrt{289 - 288}}{2} \][/tex]
[tex]\[ x = \frac{-17 \pm \sqrt{1}}{2} \][/tex]
[tex]\[ x = \frac{-17 \pm 1}{2} \][/tex]
Therefore, the solutions are:
[tex]\[ x = \frac{-17 + 1}{2} = \frac{-16}{2} = -8 \][/tex]
and
[tex]\[ x = \frac{-17 - 1}{2} = \frac{-18}{2} = -9 \][/tex]
9. Verify the solutions:
- For [tex]\(x = -8\)[/tex]:
[tex]\[ \sqrt{-8 + 9} - (-8) = \sqrt{1} + 8 = 1 + 8 = 9 \][/tex]
This is true.
- For [tex]\(x = -9\)[/tex]:
[tex]\[ \sqrt{-9 + 9} - (-9) = \sqrt{0} + 9 = 0 + 9 = 9 \][/tex]
This is also true.
Thus, the solutions to the equation [tex]\(\sqrt{x + 9} - x = 9\)[/tex] are [tex]\(\boxed{-9}\)[/tex] and [tex]\(\boxed{-8}\)[/tex].
1. Start with the given equation:
[tex]\[ \sqrt{x + 9} - x = 9 \][/tex]
2. Isolate the square root on one side of the equation:
[tex]\[ \sqrt{x + 9} = x + 9 \][/tex]
3. Square both sides of the equation to eliminate the square root:
[tex]\[ (\sqrt{x + 9})^2 = (x + 9)^2 \][/tex]
4. Simplify both sides:
[tex]\[ x + 9 = (x + 9)^2 \][/tex]
5. Expand the right side of the equation:
[tex]\[ x + 9 = x^2 + 18x + 81 \][/tex]
6. Bring all terms to one side to set the equation to zero:
[tex]\[ 0 = x^2 + 18x + 81 - x - 9 \][/tex]
7. Simplify the equation:
[tex]\[ 0 = x^2 + 17x + 72 \][/tex]
8. Solve the quadratic equation [tex]\(x^2 + 17x + 72 = 0\)[/tex].
The quadratic formula is given by [tex]\(x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\)[/tex]. Here, [tex]\(a = 1\)[/tex], [tex]\(b = 17\)[/tex], and [tex]\(c = 72\)[/tex].
[tex]\[ x = \frac{-17 \pm \sqrt{17^2 - 4 \cdot 1 \cdot 72}}{2 \cdot 1} \][/tex]
[tex]\[ x = \frac{-17 \pm \sqrt{289 - 288}}{2} \][/tex]
[tex]\[ x = \frac{-17 \pm \sqrt{1}}{2} \][/tex]
[tex]\[ x = \frac{-17 \pm 1}{2} \][/tex]
Therefore, the solutions are:
[tex]\[ x = \frac{-17 + 1}{2} = \frac{-16}{2} = -8 \][/tex]
and
[tex]\[ x = \frac{-17 - 1}{2} = \frac{-18}{2} = -9 \][/tex]
9. Verify the solutions:
- For [tex]\(x = -8\)[/tex]:
[tex]\[ \sqrt{-8 + 9} - (-8) = \sqrt{1} + 8 = 1 + 8 = 9 \][/tex]
This is true.
- For [tex]\(x = -9\)[/tex]:
[tex]\[ \sqrt{-9 + 9} - (-9) = \sqrt{0} + 9 = 0 + 9 = 9 \][/tex]
This is also true.
Thus, the solutions to the equation [tex]\(\sqrt{x + 9} - x = 9\)[/tex] are [tex]\(\boxed{-9}\)[/tex] and [tex]\(\boxed{-8}\)[/tex].
Thank you for contributing to our discussion. Don't forget to check back for new answers. Keep asking, answering, and sharing useful information. Thank you for visiting IDNLearn.com. We’re here to provide dependable answers, so visit us again soon.